A jury of her peers - Korelitz, Jean Hanff (New York : Onyx, 1997)
A legal thriller featuring Sybylla Muldoon of New York, defending a homeless man accused of slashing a schoolgirl. When an implant is discovered in his arm--he says it was inserted by people who abducted him--the lawyer sends it for tests. The tester is killed, the implant disappears.
National College of Business and Arts
Keywords: Women lawyers -- Fiction; Legal fiction (Literature)